Masculinity and the Questions of “Is” and “Ought”: Revisiting the Definition of the Notion of Masculinity Itself - Ognjen Arandjelović (Sexes, 2023)
The Oxford English Dictionary (OED) lists 1571 as the year of the first recorded use of the English word ‘masculinity’; the Ancient Greek <semantics><mover accent="true">α˘</mover>νδρϵ<mover accent="true">ι´</mover><mover accent="true">α¯</mover></semantics> (andreia), usually translated as ‘courage’, was also used to refer to manliness. The notion of manliness or masculinity is undoubtedly older still. Yet, despite this seeming familiarity, not only is the notion proving to be highly elusive, its understanding by the society being in a constant flux, but is also one which is at the root of bitter division and confrontation, and which has tangible and far-reaching real-world effects. At the same time, while masculinity has been attracting an increasing amount of attention in academia, the large body of published work seldom goes to the very foundations of the issue, failing to explicitly and with clarity reach a consensus as to how masculinity ought to be understood. Herein, I critique the leading contemporary thought, showing it to be poorly conceived and confounded, and often lacking in substance which would raise it to the level of the actionable and constructive. Hence, I propose an alternative view which is void of the observed deficiencies, and discuss how its adoption would facilitate a conciliation between the currently warring factions, focusing everybody’s efforts on addressing the actual ethical, deconfounded of specious distractions.